Sociolinguistic History, Sociolinguistic Geography and Bilingualism - Afendras, Evangelos A. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
An attempt is made to develop a method for the presentation of temporal and spatial sociolinguistic data in order to study phenomena of bilingual interaction. Domain of language usage and other sociocultural variables are abstracted from extant sources, normalized and compared with the aim of studying sociolinguistic variation, its reflection on stability of language distribution and the relation of the latter to convergence processes in the languages in contact. The possibility of applying sociological-geographic models for the diffusion of innovation to linguistic diffusion is investigated. The case of the Macedorumanian nomads in the Balkans is used to illustrate the method. (Author/DO)
ERIC Note: Paper presented at the International Days in Sociolinguistics, Istituto Luigi Sturzo, Rome, September 14-17, 1969.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Culture Contact; Diglossia; Interference (Language); Language Role; Language Usage; Mathematical Models; Migration Patterns; Bilingualism; Diachronic Linguistics; Sociocultural Patterns; Sociolinguistics; Macedorumanians